Enhancing VSSS Pose Control with Hardware Acceleration and Bio-Inspired Algorithm Optimization - Pastrana, M. A.; Luiz, Matheus de S.; Barbosa, Filipe R.; Baptista, Roberto de Souza; Munoz, Daniel M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper presents a novel approach to enhancing pose control for Very Small Size Soccer (VSSS) robots through the integration of hardware acceleration and bio-inspired optimization algorithms. The proposed system leverages Field-Programmable Gate Array (FPGA) technology to implement a PID controller with varying levels of floating-point precision (11, 16, 23, and 27 bits), enabling efficient and high-performance control. Hardware-in-the-Loop (HIL) simulations, conducted using the CoppeliaSim platform, validate the system's effectiveness, demonstrating significant improvements in control accuracy as precision increases. Two bio-inspired algorithms—Differential Evolution (DE) and Moth Flame Optimization (MFO)—are employed to fine-tune the PID parameters. Both algorithms demonstrate strong convergence, with DE achieving a fitness function value of 0.4172 and MFO reaching 0.3736. The results highlight the potential of combining FPGA-based hardware acceleration with bio-inspired optimization to address the dynamic and demanding challenges of the VSSS competition robot.